PHENOMENOLOGICAL STUDY : COMMUNITY EXPERIENCE AS A PUBLIC SERVICE AT THE PUBLIC HEALTH CENTER - Nurul Hayati (UPT Penerbitan Universitas Jember, 2017)
Background: Identify a complaints that the community needs as a service user to health services. Is an important factor to improve the improvement of health services at public health center (Puskesmas). Provision of excellent service to the community which is the embodiment of the obligations of the government apparatus as a public servant. In its implementation the service providers should implement access to public service accesses consisting of transparency, accountability, participatory, and responsiveness. The purpose of this study is to explore the community's experience in receiving puskesmas services. Methods: The research design used was qualitative with interpretive phenomenology approach. The data were collected through in-depth face-to-face interviews with 10 community members from community leaders, cadres and religious leaders. Data were collected and analyzed using thematic analysis based on Braun & Clarke approach. Results: The research yield 3 theme that is the expectation of facility convenience, less optimal of puskesmas service, and lack of service officer accessibility. Conclusions: Community experience in receiving puskesmas services is a complex experience related to the expectation of facility convenience, lack of optimal service of puskesmas, and the lack of service access of officers so as to result in improvement efforts for improvement of service based on public complaints to improve public health service quality. Exploration of community experience combined with staff experience is necessary to obtain material for policy proposals on improving the quality of public services in the health sector. Keywords: community experience, public service, puskesmas